Application of the Problem Based Learning Learning Model to the Learning Activities of Class V Students at SDN Dukuh Kupang Surabaya - Pratiwi, Desi Eka (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine student learning activities using the PBL model on energy sources in class V SDN Dukuh Kupang Surabaya. This type of research uses a descriptive qualitative research type. The subjects of this research were 26 students of class V at SDN Dukuh Kupang Surabaya. Data collection techniques carried out in this study were observation and documentation. Student learning activity data shows a percentage of 85.52% is in the very good category. So it can be concluded that the application of the PBL model can help improve student learning activities. Students during learning gave a good response to the application of the PBL model. Teachers can use the PBL model as an active, creative, effective and fun learning model for students